2017
DOI: 10.1113/jp274726
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia‐induced active expiration increases in sleep and enhances ventilation in unanaesthetized rats

Abstract: Expiration is passive at rest but becomes active through recruitment of abdominal muscles under increased respiratory drive. Hypercapnia-induced active expiration has not been well explored in unanaesthetized rats. We hypothesized that (i) CO -evoked active expiration is recruited in a state-dependent manner, i.e. differently in sleep or wakefulness, and (ii) recruitment of active expiration enhances ventilation, hence having an important functional role in meeting metabolic demand. To test these hypotheses, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 56 publications
1
30
2
Order By: Relevance
“…Other studies, however, have reported different results concerning the occurrence of active expiration during sleep. Although Leirão, Silva, Gargaglioni, and da Silva () have demonstrated that NREM sleep is accompanied by robust active expiration in hypercapnia‐exposed rats, these authors showed that rats breathing room air did not present active expiration during this sleep state. Likewise, we did not observe expiratory abdominal muscle recruitment during sleep in our recordings.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies, however, have reported different results concerning the occurrence of active expiration during sleep. Although Leirão, Silva, Gargaglioni, and da Silva () have demonstrated that NREM sleep is accompanied by robust active expiration in hypercapnia‐exposed rats, these authors showed that rats breathing room air did not present active expiration during this sleep state. Likewise, we did not observe expiratory abdominal muscle recruitment during sleep in our recordings.…”
Section: Discussionmentioning
confidence: 92%
“…The pre‐Bötzinger complex (pre‐BötC), located in the ventral medulla, is responsible for generating the active inspiratory motor behaviour (Smith, Ellenberger, Ballanyi, Richter, & Feldman, ). During high chemical drive, such as increases in CO 2 (hypercapnia) and/or in [H + ] (acidosis), expiratory muscles contract to force exhalation during stage 2 of expiration, thereby enhancing pulmonary ventilation (Abdala, Rybak, Smith, & Paton, ; Leirao, Silva, Gargaglioni, & da Silva, ; Magalhaes et al., ; Pisanski & Pagliardini, ). This phenomenon is mediated by phasic late‐expiratory (late‐E) neurons located in the parafacial respiratory group (pFRG), adjacent to the ventrolateral portion of the facial nucleus in rats (Abdala et al., ; Pagliardini et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect seems to be exclusive to hypoxia, because ablation of the C1 cells did not affect the generation of active expiration elicited by hypercapnia. These results suggest that recruitment of Abd muscles by chemosensory drives could be mediated through different neuromodulatory systems (Leirão et al, 2018;O'Halloran, 2018).…”
Section: Hypoxia Triggering Active Expiration Depends On C1 Cellsmentioning
confidence: 81%